Mesoporous-silica induced doped carbon nanotube growth from metal–organic frameworks. Issue 13 (20th March 2018) - Zhou, Huang; He, Daping; Saana, Amiinu Ibrahim; Yang, Jinlong; Wang, Zhe; Zhang, Jian; Liang, Qirui; Yuan, Shuai; Zhu, Jiawei; Mu, Shichun
Abstract : Small diameter cobalt and nitrogen co-doped carbon nanotubes (Co/N-CNTs) were grown from a mesoporous-silica (mSiO2 ) covered Co-based MOF (ZIF-67). Abstract : Carbon materials, with a controllable structure, derived from metal–organic frameworks (MOFs) have emerged as a new class of electrocatalysts in renewable energy devices. However, efficient conversion of MOFs to small diameter doped carbon nanotubes in inert gases at high temperatures (>600 °C) remains a significant challenge. In this study, we first report the growth of small diameter cobalt and nitrogen co-doped carbon nanotubes (Co/N-CNTs) from mesoporous silica (mSiO2 )-coated Co-based MOFs (ZIF-67). The presence of a layer of mSiO2 outside the ZIF-67 nanocrystals prevents the Co nanocatalysts from quick aggregation, and significantly serves as a unique 'sieve' for inducing the catalytic growth of CNTs during pyrolysis. The obtained Co/N-CNTs, with ∼13 nm diameter evolved from the pristine MOF architecture, exhibit higher catalytic activity and stability for oxygen reduction than commercial Pt/C electrocatalysts in alkaline media. This novel strategy opens a new avenue for the synthesis of Co/N-CNTs with great promise for developing high performance and cheap electrocatalysts.